2016
DOI: 10.1039/c5tx00331h
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl chain modulated cytotoxicity and antioxidant activity of bioinspired amphiphilic selenolanes

Abstract: A series of amphiphilic conjugates of dihydroxy selenolane (DHS) and monoamine selenolane (MAS), which we had previously reported to inhibit lipid peroxidation and assist the oxidative protein folding reaction respectively in cell free systems, were evaluated for cytotoxicity, associated mechanisms and antioxidant effects in cells. Our results indicated that a fatty acid/alkyl group of variable chain lengths (C) as a lipophilic moiety of the DHS/MAS conjugates not only improved their ability to incorporate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Approximately, 2 μg of the total RNA was used for cDNA synthesis by reverse transcription (cDNA synthesis kit, Thermo Scientific, USA), and real-time PCR was carried out using the template (cDNA), SYBR green master mix (Roche Applied Science, Germany), and gene-specific primers in a Rotor-Gene Q (QIAGEN, Germany), according to the protocol standardized earlier. 51 The threshold cycle (CT) values estimated from the above runs for the target genes were normalized against a housekeeping gene, b-actin, according to the method described earlier. 52 The primers (forward and reverse) used for cDNA amplification are γGCL (forward): 5′-GGGGTGACGAGGTGGAGTA-3′, γGCL (reverse): 5′-GTTGGGGTTTGTCCTCTCCC-3′, βActin (forward): 5′-GGCTGTATTCCCCTCCATCG-3′, and βActin (reverse): 5′-CCAGTTGGTAACAATGCCATGT-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 2 μg of the total RNA was used for cDNA synthesis by reverse transcription (cDNA synthesis kit, Thermo Scientific, USA), and real-time PCR was carried out using the template (cDNA), SYBR green master mix (Roche Applied Science, Germany), and gene-specific primers in a Rotor-Gene Q (QIAGEN, Germany), according to the protocol standardized earlier. 51 The threshold cycle (CT) values estimated from the above runs for the target genes were normalized against a housekeeping gene, b-actin, according to the method described earlier. 52 The primers (forward and reverse) used for cDNA amplification are γGCL (forward): 5′-GGGGTGACGAGGTGGAGTA-3′, γGCL (reverse): 5′-GTTGGGGTTTGTCCTCTCCC-3′, βActin (forward): 5′-GGCTGTATTCCCCTCCATCG-3′, and βActin (reverse): 5′-CCAGTTGGTAACAATGCCATGT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, total RNA was isolated from cells at 48 h after treatment with HS or its derivatives using the TRI reagent. Approximately, 2 μg of the total RNA was used for cDNA synthesis by reverse transcription (cDNA synthesis kit, Thermo Scientific, USA), and real-time PCR was carried out using the template (cDNA), SYBR green master mix (Roche Applied Science, Germany), and gene-specific primers in a Rotor-Gene Q (QIAGEN, Germany), according to the protocol standardized earlier . The threshold cycle (CT) values estimated from the above runs for the target genes were normalized against a housekeeping gene, b-actin, according to the method described earlier .…”
Section: Methodsmentioning
confidence: 99%
“…While for DMSNs-EB treated cells, a significantly lower cell viability was observed compared to the DMSNs-BB-1 group, suggesting the higher cytotoxicity of DMSNs-EB than DMSNs-BB-1 and the potential of DMSNs-BB-1 as biocompatible cellular delivery vehicles. The end hydrophobic organic groups have been reported to disrupt cell membrane and cause cell cytotoxicity, while MONs with bridged hydrophobic organic groups in the framework possess better hemocompatibility and lower cytotoxicity. , Here, we directly compared the cytotoxicity difference between DMSNs-EB and DMSNs-BB-1 with end and bridged benzene groups, respectively. The higher cytotoxicity of DMSNs-EB than DMSNs-BB-1 suggests that compared to the bridged benzene group covalently connected to two silicon atoms, the end benzene group modified on the surface of DMSNs is more effective in disrupting the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that antioxidant molecules protect against TAA‐induced oxidative stress . It has also been reported that selenium compounds possess numerous biological properties, mainly associated with their ability to modulate the expression of selenoenzymes such as glutathione peroxidase (GPx) and thioredoxin reductase …”
Section: Introductionmentioning
confidence: 99%
“…[15,16] It has also been reported that selenium compounds possess numerous biological properties, mainly associated with their ability to modulate the expression of selenoenzymes such as glutathione peroxidase (GPx) and thioredoxin reductase. [17,18] The main studied selenium compounds, Diphenyl diselenide and Ebselen, have been reported as promising antioxidant molecules mainly due to their GPx-like activity. [19] In this regard, new diselenides F I G U R E 1 Chemical structure of -selenoamines and monoselenides molecules are designed using DPDS and Ebs, respectively, as a prototype structure.…”
Section: Introductionmentioning
confidence: 99%